Developing guidelines for selection-deselection in high performance sport for athletes, coaches, and organisations: A delphi study - Slade, K.; Jowett, S.; Rhind, D. (Journal of Sports Sciences, 2024)
The process of athlete selection and deselection in sport involves not only athletes but also coaches, managers, performance directors, talent pathway coordinators and the wider organisation. Athlete selection and deselection can be viewed as the opposite sides of the same coin in that the process may be the same for all athletes but the outcome is very different. The outcome of this process can evoke extremely powerful emotions ranging from elevation to devastation. While selection and deselection are part of competitive sport regardless of type, level, gender or age, research is scarce. Employing the Delphi method, a total of 20 participants comprised the expert panel (coaches, athletes and other key personnel in high performance) from various sports, and ages ranged from 21 to 59 years old. Following three rounds, 60 items reached the pre-determined consensus level of 75%. The 60 items were then further content analysed and grouped with respect to the three key stakeholders: athlete (14), coach (21) and organisation (25). Within each of these categories, subcategories emerged: personal, interpersonal, procedural, educational, supportive, communicative and reviewing behaviours and actions that athletes, coaches and organisations can take to ease the navigation, apply consistency and establish a common ground during this challenging situation.